IgG4-related Disease Manifesting as Autoimmune Pancreatitis, Sialadenitis, and Cholangitis: Case Report - Augustina Tumelytė; Vytautas Rimkus; Paulina Tekoriutė; Limas Kupčinskas (Acta Medica Lituanica)
IgG4-related disease (IgG4-RD) is a rare autoimmune disease which can affect almost any organ. We present a case of IgG4-RD, which manifested as chronic autoimmune pancreatitis with pancreatic insufficiency, severe malnutrition, autoimmune sialadenitis, and cholangitis. After the administration of prednisolone and mycophenolate mofetil, the patient’s condition improved significantly.